A new framework for Bible translation - T. Wilt (Acta Theologica)
Since the time in which Nida and Taber published The theory and practice of translation, there have been dramatic changes in the communication situations of Bible translation throughout the world. Further, advances in a variety of academic disciplines have enabled us to recognise and move beyond shortcomings of that work’s portrayal of language, communication and translation. A recent project by the United Bible Societies has attempted to provide a more contemporary framework for understanding Bible translation. This paper focuses on the communication model developed for this project. Avoiding the fallacy of the conduit metaphor of communication, it explicitly refers to the goals of the participants in a communication situation and the organisational as well as sociocultural frames within which texts are produced and perceived. The framework suggested by this model encourages viewing translation as a process involving churches, communities and publishers as well as translators and choosing a particular translation approach in terms of mutually agreed upon goals. The Bible translation process may involve not just producing a text to represent the sacred text, but also supplementary texts to enhance understanding and appreciation of both the translation and the translated.